Perkembangan Populasi Nematoda Puru Akar (Meloidogyne spp.) dan Tingkat Kerusakan Pada Beberapa Tanaman Familia Solanaceae - NURUL KHOTIMAH; I NYOMAN WIJAYA; MADE SRITAMIN (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2020)
Development Population of Root-Knot Nematode (Meloidogyne spp.) and TheLevel Of Damage to Some Plants Solanaceae Family This research started from November 2018 until March 2019 in the experimental garden Pegok Faculty of Agriculture, University Udayana. It uses acomplete randomized design with 4 treatments and 6 repeats. The study treatmentuses some of the Solanaceae family plants such us tomato (Lycopersiconesculentum), eggplants (Solanum melongena L), large red chili pepper (Capsicumannum), cayenne pepper (Capsicum frutescens), which was given 500 of nematodesMeloidogyne spp. on Each polybag. The observed parameters include thedevelopment of the population of nematode Meloidogyne spp. for 2 life cycles in 1gram of root and 300 grams of soil and measuring the rate of crop damage.Nematodes Meloidogyne spp. is an important parasitic nematodes in the world.Solanaceace plants are widely cultivated in Indonesia because of their high economicvalue and become an important food ingredient. One of the problems in aquacultureSolanaceae is the attack nematodes Meloidogyne spp.. The highest population of theresearch results is in tomato plants with a damage rate of 68.3%. The lowestpopulation amount in chili pepper plants with a damage rate of 11.7%. The less-likedplant Nematoda Meloidogyne spp. is a chili pepper so it can be used as an alternativecrop rotation.